Políticas socioeducativas no contexto brasileiro: uma revisão bibliográfica - Pinheiro, Nichy Lyss Belarmino (Brasil, 2021)
The proposal that constitutes the Course Conclusion Paper - TCC, entitled: "The production of socio-educational policies in Brazil and its implications in the discussion on education, human rights and the identity of minor offenders", has as its central objective to understand the historical and socio-educational construction of policies and practices aimed at socioeducational assistance to minor offenders, taking into account the discussions on education as a process of social transformation. Therefore, we opted for the qualitative research by Rey (2005). As for qualitative research, Rey states that this methodological approach “[...] represents a permanent process, within which all decisions and methodological options are constantly defined and redefined during the research process itself” (2005 p. 81). The instrument for the production of the work in question appropriates the literature review, following the data collection parameters listed by Severino (2007). Education as a basis for the process of social reintegration of these minors who entered the context of marginality and criminality, has as social and political functionality, not only the reception, but the role of transforming and empowering the minor offender subject. Social education then becomes a pedagogical element of social, educational and citizen formation. In this sense, empowerment based on the real life aspects of these subjects allows educators to act through everyday elements that involve political and academic knowledge as a structure for their pedagogical practice. Understand and perceive these subjects (minor offenders) as subjects of rights, able to look at their way of life (race, social class, family context) and, at the same time, at the social intricacies that make up their living and being in the world , in society allows the educational context to enable new social identities for these subjects. Therefore, articulated education and discussions on human rights as a process of citizen education, transformed, and equity, allowed us to look at public policies that directly and indirectly infer in the context of socio-educational care as an instrument that standardizes, normalizes and also produces elements of social reintegration as an act of resistance and social transformation both for minor offenders and for society itself.